O Seguinte Olhar: estudo de caso de um processo criativo em dança com uma bailarina deficiente visual - MOTA, Marina Alves (Universidade Federal do Pará, 2017)
This study aims to reserch the creative process of O Seguinte Olhar dance show, performed with the visually impaired dancer Socorro Lima, a member of dance group Passos Para Luz, which develops works with visually impaired people in the city of Belém do Pará for ten years. This is a study case. The paper try to analyze the scenic construction of the body, still considered incapable for such practice, in order to allow new perspectives about movement, creation, production and reception artistic focused on visually impaired person. The meetings happened from August to December 2012 three times a week and lasting three hours a day. The techniques used to colect pieces of information in the research envolves the use of audiovisual records, photographic, notes made in locus, unstructured interviews and testimonials of the team that wrote the researched show. From the analysis of the show O Seguinte Olhar lays emphasis to the possibility to ways of creation and reception in dance facing people with visual impairment.